ACTION BETWEEN TEACHER AND STUDENTS IN LEARNING ENGLISH AT GRADE XI OF MAN SERDANG BEDAGAI - Indah Nurhasanah; Isli Iriani Indiah Pane; Rafika Dewi Nasution (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
The aim of this study were to figure out the dominant category used by teacher and students and the types of verbal interaction used by teacher and students in learning English at grade XI of MAN Serdang Bedagai. The methodology of this study is descriptive qualitative research. The researcher took two classes (XI-IPA2 and XI-IPS2). The researcher used observational tally sheet, matrix, and audio recording as the instruments for collecting the data. The data were analyzed by using Flanders’ Interaction Analysis Category System (FIACS). The data analysis showed that the teacher more dominant in the classroom interaction than the students. The percentage of teacher talk in class XI-IPA2 was 74.03%, in class XI-IPS2 was 65.60%. The dominant category used by teacher in class XI-IPA2 was lecturing by 31.78%, in class XI-IPS2 was also lecturing by 24.73%. The percentage of student talk in class XI-IPA2 was 20.16%, in class XI-IPS2 was 26.88%. And the dominant category of student talk was student talk-response with 15.11% in class XI-IPA2 and 23.65% in class XI-IPS2. All the types of verbal interaction based on Flanders’ Interaction Analysis Category System (FIACS) occurred in the classroom during teaching and learning process at grade XI of MAN Serdang Bedagai.Keywords: Verbal interaction, teacher talk, student talk, Flanders’ Interaction Analysis Category System (FIACS)